Quark model description of quasi-elastic pion knockout from the proton at JLAB - Obukhovsky I. T.; Fedorov D.; Faessler A.; Gutsche Th.; Lyubovitskiy (Lyubovitskij) V. E. Valery Efimovich (2006, 2006)
Title screen